Dual Function of l‐Phenylalanine as a Modification Layer toward Enhanced Device Performance and Mitigated Lead Leakage in Perovskite Solar Cells. Issue 2 (4th December 2022) - Zhang, Yang; Han, Yipeng; Liu, Xufu; Kong, Tengfei; Song, Jing; Xie, Haibing; Bi, Dongqin
Abstract : Although perovskite solar cells have achieved great breakthroughs in photoelectric conversion efficiency (PCE), some challenges still need to be addressed before commercialization. Lead leakage is harmful to the environment and many methods are developed to prevent lead leakage; among them, chemical adsorption has proved to be an effective way. Herein, a simple and low‐cost strategy that can enhance the device performance and mitigate the lead leakage by applying l ‐phenylalanine in the interface of NiO x /perovskite is reported. The results show that this strategy can improve the morphology and conductivity of the NiO x film, optimize the NiO x /perovskite interface energy level, resulting in an efficient and stable device with a PCE of 19.0%. Furthermore, the interface modification improves the stability of the perovskite film through strong interaction with the perovskite, inhibits the decomposition of the film in water, slows down the process of lead leakage, and protects the environment from lead pollution. The devices maintain 86% initial efficiency for 200 h maximum power point measurement and 94% for 2100 h under nitrogen. Abstract : l ‐Phenylalanine (l ‐Phe) as a passivation layer at NiO x /perovskite interface can improve the morphology and conductivity of the NiO x film, promote carrier transport at the interface, and enhance the performance of perovskite films. Furthermore, the passivated device effectively slows down the lead leakage process in water through strong interaction with perovskite.